The Role of Leadership in Implementation Public Information System of Local Government Institutions in Indonesia - Dewi, Nurlia; Abdillah, Willy; Salim, Muhartini; Widodo, Slamet (International Review of Management and Marketing, 2021)
Leadership style is one of the triggers for individuals to be motivated to work, increase their dedication to work, influence the ideal work process, and produce optimal work performance (Bass and Avolio, 1993). This study will look at the relationship between the variables of the influence of leadership, system quality, service quality and information quality on net benefits through a quantitative research survey using primary data in the form of a questionnaire taken directly from research respondents with the population coming from the state civil apparatus representing each device organization. in the district and city administrations of the Bengkulu province in Indonesia. Data collection was carried out by census, as many as 292 people and data analysis using Partial Least Square with the help of SmartPLS software. The results showed that the transformational leadership and information quality had no effect on the use of Information Management and Documentation Officer (PPID) software, system quality and service quality affected the use of the PPID system, the use of the PPID system had an effect on user satisfaction with the PPID system, and the satisfaction of PPID system users had an effect on to net benefits (PPID system performance). The results of this study provide an understanding of the implementation of organizational information system management practices to improve information technology, especially those related to the variables in this study. Practically, PPID policy makers can improve the quality of the information system by modifying and improving features that are still inadequate, such as detailed information on information recorded in the PPID software. Keywords: leadership, system quality, system use, service, information, and benefits. JEL Classifications: M38 DOI: https://doi.org/10.32479/irmm.12515